THE APPLICATION OF THE EXAMPLE OF THE JESUS CHRIST AS THE GREAT TEACHER ACCORDING TO JOHN 13:1-17 - Joko Prihanto; Victor Deak; Josep Tatang (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
In education, students will show their character or attitude in life according to what they get from the person who teaches and guides them. The example of a teacher's life is very emphasized to be applied so that students can see a good example or example. An example of life is more important than a thousand theories or a thousand beautiful words of wisdom because an example is not just a concept or theory but an action. Good and successful educators are educators who teach theory which can then be realized in practical actions to strengthen the theory that has been taught. In all circumstances, a teacher or teacher is required to be an example for his students. The Lord Jesus Christ is an example or example that must be followed by teachers who want to be successful in teaching. The Lord Jesus Christ is the center of all examples in Christian education. Embodied truth is the only truth that matters. The example of a teacher's life is to complete all his teaching. The teacher is like the "stick of Moses" that God can use to build God's people to know God better. The qualifications of teachers of Christian religious education are very dependent on spiritual personality, mental, and social qualities that imitate the leader or the Great Teacher, namely Jesus Christ. Further followed by the intellectual authority of knowledge and wisdom. This study uses descriptive qualitative research methods. Research provides new knowledge and understanding to Christian teachers that a Christian teacher must have biblical qualifications and can be an example in his life.